Tomatoes - (:unkn) unknown (My University, 2009)
Vegetable sellers of East Indian origin display their vegetables for sale on a roadside vending stand. The postcard stamped by the Tourism Inquiry Board, Trinidad, B.W.I.
Colour: Black and white;Style:Landscape;Other:Bordered,Divided
Keywords: Postcards; Trinidad and Tobago; Street vendors; East Indians; Vending stalls; Vegetables